Relokasi Hypocentre Gempa Bumi Dengan Velest (JHD) dan Estimasi Sesar Daerah Sumatra Selatan: Irwansyah Ramadhani, Bagus Jaya Santosa - Irwansyah Ramadhani Irwansyah Ramadhani; Bagus Jaya Santosa Bagus Jaya Santosa (Jurnal Fisika dan Aplikasinya, 2017)
Earthquake is an unpredictable natural phenomena in occurance which has harmfull consequences. In high magnitude, it can cause other disaster i.e. tsunami which result in hard demage infrastructure and loss of population. One can not determine earthquake presence exactly, however can estimate earthquake prone zone, major hard demage zone, and next earthquake presence. They can be estimated through hypocentre determination and earths model. Velest is an JHD ((Join Hypocentre Determination) based method which applies all events to inverted simultaneously and results true hypocentre of earthquake. In other hand, Velest can determine one dimensional earths model based P and S wave travel time data. Then, earths characteristic can be determined by ISOLA. It is able to provide an imaging of fault in a research area through moment tensor. Both Velest and ISOLA applies in this research. Arrival time of P wave is analized by STFT and CWT algorithm. Then, Velest applies to earthquake events relocation while ISOLA applies to determine earths characteristic (fault) inSouthern Sumatra. This research note that velest is able to determine true hypocentre of earthquake well and one dimensional earth model of South Sumatra. In other hand, moment tensor of 4 events show geometry of fault in Souther Sumatra is dip-slip.